Effects of the kappa opioid receptor antagonist nor‐binaltorphimine (nor‐BNI) on cocaine versus food choice and extended‐access cocaine intake in rhesus monkeys. (8th January 2015) - Hutsell, Blake A.; Cheng, Kejun; Rice, Kenner C.; Negus, Sidney Stevens; Banks, Matthew L.
Abstract: The dynorphin/kappa opioid receptor (KOR) system has been implicated as one potential neurobiological modulator of the abuse‐related effects of cocaine and as a potential target for medications development. This study determined effects of the KOR antagonist nor‐binaltorphimine (nor‐BNI) on cocaine self‐administration under a novel procedure that featured two daily components: (1) a 2‐hour 'choice' component (9:00–11:00am ) when monkeys could choose between food pellets and cocaine injections (0–0.1 mg/kg per injection, intravenous) and (2) a 20‐hour 'extended‐access' component (noon to 8:00am ) when cocaine (0.1 mg/kg per injection) was available under a fixed‐ratio schedule to promote high daily cocaine intakes. Rhesus monkeys ( n  = 4) were given 14 days of exposure to the choice + extended‐access procedure then treated with nor‐BNI (3.2 or 10.0 mg/kg, intramuscular), and cocaine choice and extended‐access cocaine intake were evaluated for an additional 14 days. Consistent with previous studies, cocaine maintained both a dose‐dependent increase in cocaine choice during choice components and a high level of cocaine intake during extended‐access components. Neither 3.2 nor 10 mg/kg nor‐BNI significantly altered cocaine choice or extended‐access cocaine intake. In two additional monkeys, nor‐BNI also had no effect on cocaine choice or extended‐access cocaine intake when it was administered at the beginning of exposure to the extended‐access components. Overall, these results do not support a major role for the dynorphin/KOR system in modulating cocaine self‐administration under these conditions in non‐human primates nor do they support the clinical utility of KOR antagonists as a pharmacotherapeutic strategy for cocaine addiction. Abstract : The dynorphin/kappa‐opioid receptor system has been implicated as one potential neurobiological modulator of cocaine abuse‐related effects. Rhesus monkeys (n=4) behaved under a novel cocaine vs. food choice + extended cocaine access procedure and then treatment with the kappa‐opioid receptor antagonist nor‐BNI (3.2 or 10 mg/kg, intramuscular). Neither 3.2 nor 10 mg/kg nor‐BNI significantly altered cocaine choice or extended‐access cocaine intake. Overall, these results do not support a role for the dynorphin/kappa‐opioid receptor system in modulating cocaine self‐administration in monkeys.